The Paradigm of State Legal Policy Towards The Government's Role in Institutional Strengthening of Microfinance Institutions: A Social Welfare Approach - Muin, Fatkul (Innovative: Journal Of Social Science Research, 2024)
This research focuses on the role of state legal policy towards microfinance institutions that have a strategic function in order to meet the needs of micro-enterprises as a constitutional obligation enshrined in the provisions of the 1945 Constitution of the Republic of Indonesia. As a large country, the problem of poverty is a major problem in society, this problem can certainly be resolved by the state carrying out its duties properly through a coaching system for the community with a micro-enterprise approach as an effort to create social welfare and equity for the community. The paradigm of social justice is inseparable from efforts to provide equal opportunities for the community to have a business, therefore state legal policy through the Law of the Republic of Indonesia Number 4 of 2023 concerning Development and Strengthening of the Financial Sector, Law of the Republic of Indonesia Number 1 of 2013 concerning Microfinance Institutions and Government Regulation Number 89 of 2014 concerning Loan Interest Rates or Financing Yields and Business Area Coverage of Microfinance Institutions, is a form of legal policy. The essence is not only the norms that regulate it, but rather the implementation in an effort to fulfil people's rights in trying to map Microfinance Institutions as financial institutions for the benefit of micro businesses. This research uses qualitative research with a legal approach.